Analisis Pengaruh Jumlah Uang Beredar dan Kurs Rupiah Terhadap Inflasi di Indonesia - Anilah, Feti; Abidatul Kamillah; Drajat Stiawan (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The purpose of this study is to find out whether the money supply and the rupiah exchange rate can have an effect on inflation for the 2017-2021 period. This study uses a quantitative method with an associative approach. The test results on the money supply variable are -9.552252 and a significance of 0.0000. The test results on the exchange rate variable are -2.581866 with a significance of 0.0124. And the f test results produce a value of 77.29357. Partially the money supply and exchange rate have a negative and significant effect on inflation and simultaneously the money supply and the rupiah exchange rate have a positive effect on inflation. In theory, a negative result indicates that the more money in circulation and the higher the rupiah exchange rate, the lower the inflation. This was caused by the covid-19 pandemic resulting in sluggishness in money circulation.